Embedding explained jury verdicts in the English criminal trial. (December 2017) - Coen, Mark; Doak, Jonathan
Abstract : English juries do not provide reasons for their verdicts. This paper argues that transparency is a fundamental value in modern decision making, and that reform is needed to trial by jury so that verdicts are routinely accompanied by explanations. It examines the options that exist to incorporate explained verdicts in the English criminal trial and concludes that accountability and legitimacy would be enhanced through the use of a trained, independent lay facilitator to chair the deliberation process and draft an explained verdict.